One-Step Synthesis of Ag2O/Fe3O4 Magnetic Photocatalyst for Efficient Organic Pollutant Removal via Wide-Spectral-Response Photocatalysis–Fenton Coupling - Chuanfu Shan; Ziqian Su; Ziyi Liu; Ruizheng Xu; Jianfeng Wen; Guanghui Hu; Tao Tang; Zhijie Fang; Li Jiang; Ming Li (Molecules, 2023)
Photocatalysis holds great promise for addressing water pollution caused by organic dyes, and the development of Ag2O/Fe3O4 aims to overcome the challenges of slow degradation efficiency and difficult recovery of photocatalysts. In this study, we present a novel, environmentally friendly Ag2O/Fe3O4 magnetic nanocomposite synthesized via a simple coprecipitation method, which not only constructs a type II heterojunction but also successfully couples photocatalysis and Fenton reaction, enhancing the broad-spectrum response and efficiency. The Ag2O/Fe3O4 (10%) nanocomposite demonstrates exceptional degradation performance toward organic dyes, achieving 99.5% degradation of 10 mg/L methyl orange (MO) within 15 min under visible light irradiation and proving its wide applicability by efficiently degrading various dyes while maintaining high stability over multiple testing cycles. Magnetic testing further highlighted the ease of Ag2O/Fe3O4 (10%) recovery using magnetic force. This innovative approach offers a promising strategy for constructing high-performance photocatalytic systems for addressing water pollution caused by organic dyes.